First description of the male of Alopecosa azsheganovae Esyunin, 1996 (Araneae: Lycosidae) - Azarkina, Galina N.; Marusik, Yuri M.; Antonenko, Tatyana V. (Zootaxa, 2015)
Alopecosa azsheganovae Esyunin, 1996 was described based on three females from Troitsk Wildlife Sanctuary (South Ural). This species was placed into the pulverulenta species group sensu Kronestedt (1990). After its description, it has been considered only in one publication by Esyunin & Tuneva (2012), who reported and illustrated two large (compared to the type series) females from the type locality. While studying material from Western Siberia, we found samples containing both sexes of A. azsheganovae. Therefore, we decided to redescribe the female and describe the previously unknown male of this species.